PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN ADMINISTRASI PEMBANGUNAN SETDA KABUPATEN BIMA - Jihan Fahirat; Mulyadin Mulyadin (LP2M Universitas Bina Bangsa, 2021)
High workload and work stress can affect employees who double hold a job that is not actually part of it, employees also become ineffective when doing the job as they should. This study aims to know and analyze the influence between workload and work stress on employee performance in the development administration section of SETDA Bima Regency. This type of research is associative. The research instrument used is a likert scale questionnaire that has been shared. The population used in this study is employees in the development administrationof SETDA Bima Regency as many as 33 people, consisting of civil servants as many as 23 people, regional honorees as many as 7 people, volunteer staff as many as 3 people. The number of samples used in this study is as many as 33 people with a sample determination technique that is saturated sampling. Tenik data collection used is observation, interview, questionnaire, documentation and literature studies. Data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results showed that overall workload and work stress had a significant effect on employee performance in the development administration of BIMA Regency SETDA.